PENGARUH METODE EKSPERIMEN TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS X PADA MATERI GERAK LURUS - Azka, Millati; Sudarmanto, Agus; Yusufiyah, Hesti Khuzaimah Nurul (Physics Education Research Journal, 2020)
This study aims to examine the effect of experimental method on student learning motivation and student learning outcomes on rectilinear motion material in grade X at MAN Kendal. This is a quantitative research with a sample of 34 students of class X MIPA 4 as an experimental group and 32 students of class X MIPA 2 as a control group. Data collection techniques using test, questionare, observation, interview, and documentation. The experimental class is given learning using experimental methods and control classes using conventional methods. The hypothesis was tested using t test and simple linear regression. The results of hypothesis test show that learning motivation of the experimental class students is higher than the control class and learning outcomes of the experimental class are better than the control class. Based on the results of data analysis, it was concluded that there was a correlation between the experimental method of student motivation and learning outcomes.